Preliminary study : flood awareness training preparation using serious games - Nursyahida Mokhtar; Amirah Ismail; Zurina Muda (Penerbit Universiti Kebangsaan Malaysia, 2018)
Serious games are games that educate, train and enlighten by using the entertainment principle, creativity and technology. Serious games can provide efficient training in a safe and relatively inexpensive immersive environment. Therefore, it is believed that serious games have the potential to be used in flood training. Flood is a common disaster that happens every year in Malaysia. However, the level of civilians’ awareness of flood preparation is still low, while the existing method does not achieve the objectives of The Malaysia Civil Defence Force (APM). The objective of this paper is to present an analysis of flood awareness training preparation among the Malaysians, the existing method on dissemination flood information awareness and the need for technology requirements to carry out the flood awareness training preparation from the experts’ perspective. Data was gathered in this study by using the semi structured interview method. Future studies will provide further evidence on the positive impact of using a serious game for flood training preparation, and take into a consideration for the best approach to develop a serious game for flood training to provide and create awareness to the civilians regarding the importance of flood preparedness.